Cost of Respiratory Syncytial Virus Infections in US Infants: Systematic Literature Review and Analysis. (15th August 2022) - Bowser, Diana M; Rowlands, Katharine R; Hariharan, Dhwani; Gervasio, Raíssa M; Buckley, Lauren; Halasa-Rappel, Yara; Glaser, Elizabeth L; Nelson, Christopher B; Shepard, Donald S
Abstract: Background: Limited data are available on the economic costs of respiratory syncytial virus (RSV) infections among infants and young children in the United States. Methods: We performed a systematic literature review of 10 key databases to identify studies published between 1 January 2014 and 2 August 2021 that reported RSV-related costs in US children aged 0–59 months. Costs were extracted and a systematic analysis was performed. Results: Seventeen studies were included. Although an RSV hospitalization (RSVH) of an extremely premature infant costs 5.6 times that of a full-term infant ($10 214), full-term infants accounted for 82% of RSVHs and 70% of RSVH costs. Medicaid-insured infants were 91% more likely than commercially insured infants to be hospitalized for RSV treatment in their first year of life. Medicaid financed 61% of infant RSVHs. Paying 32% less per hospitalization than commercial insurance, Medicaid paid 51% of infant RSVH costs. Infants' RSV treatment costs $709.6 million annually, representing $187 per overall birth and $227 per publicly funded birth. Conclusions: Public sources pay for more than half of infants' RSV medical costs, constituting the highest rate of RSVHs and the highest expenditure per birth. Full-term infants are the predominant source of infant RSVHs and costs.